Properties of microfibrillar cellulose filled thermoplastic natural rubber: Morphology, mechanical properties, and melt flow index - Ihda Novia Indrajati; Indiah Ratna Dewi; Dwi Wahini Nurhajati (Majalah Kulit, Karet, dan Plastik, 2020)
Microfibrillar cellulose (MFC) was derived from local pineapple leaf fiber (PALF) and employed as filler in thermoplastic natural rubber (TPNR), that was a blend of natural rubber (NR) and polypropylene (PP). The blends were prepared by dynamic vulcanization. The performance of MFC-filled TPNR on morphology, mechanical properties, aging behavior, and melt flow index (MFI) were evaluated in this study. MFC was synthesized through several processing steps, including extraction, bleaching, acid hydrolysis, and ball-milling mechanical treatment. The blends were made in a fixed ratio of 60/40 (NR/PP) with various fiber concentration. The blending of NR/PP was performed by Rheomix internal mixer at 160 °C for 15 minutes with turning rotor of 90 rpm. The results showed that the particle size distribution of MFC was rather broad with some web-like agglomerates. An improvement in tensile strength was observed at low fiber loading. Fiber improved the tear strength, but decreased the elongation at break as expected. The hardness was independent to fiber loading. The morphology of fractured sample of TPNR showed fibrous structure indicating plastic deformation. MFC decreased the melt flow index of TPNR. The MFI value ranges between 3 – 5 g/10 min. One phr of MFC resulted in ultimate mechanical properties with considerable melt flow.